2022
DOI: 10.3390/ijerph19052569
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the COVID-19 Knowledges and Behavior Questionnaire in a French Population (CoVQuest-CC)

Abstract: Background: The SARS-CoV-2 pandemic has led most countries to take restrictive measures affecting social activities and individual freedoms to limit viral transmission. It was shown that practical, motivational and social barriers impact on adherence to the isolation and social distancing measures advocated by the health authorities. The purpose of this study was to develop and validate a COVID-19 Knowledges and Behavior Questionnaire adapted to a teenager and adult French population. Methods: CoVQuest-CC was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Likewise, the validation of an Indian questionnaire to assess knowledge, attitude, practices and concerns regarding COVID-19 vaccination among the general population was based on 201 participants and resulted in an alpha Cronbach coefficient of 0.86. With the exception of a french questionnaire aimed to assess COVID-19 knowledge and behaviors that was validated on a big cohort of 8045 participants [ 9 ], our study fits the current international scientific landscape for the population sample as well as validity results.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Likewise, the validation of an Indian questionnaire to assess knowledge, attitude, practices and concerns regarding COVID-19 vaccination among the general population was based on 201 participants and resulted in an alpha Cronbach coefficient of 0.86. With the exception of a french questionnaire aimed to assess COVID-19 knowledge and behaviors that was validated on a big cohort of 8045 participants [ 9 ], our study fits the current international scientific landscape for the population sample as well as validity results.…”
Section: Discussionmentioning
confidence: 90%
“…Worldwide, countries with high vaccination rates validated COVID-19 knowledge and behavior questionnaires (France [ 9 ], Spain [ 10 ], Italy [ 11 ], Hungary [ 12 ], Brazil [ 13 ], Korea [ 14 ], India [ 15 ], etc.). Timely insights from behavioral and attitudinal data proved to be crucial for the decision-making process in the COVID-19 international public health policies [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For these 3 concept areas, all response modalities are offered in the form of a Likert scale. The precise content of the CovQuest-CC questionnaire is presented elsewhere [19]. The questionnaire was psychometrically tested and validated in a general population aged 10 years and older.…”
Section: Recruitmentmentioning
confidence: 99%
“…The following age groups were represented: 10-19, 20-29, 30-39, 40-49, 50-59, 60-69, 70-79, 80-89, and >90 years. As explained in a previous report on the CovQuest-CC questionnaire validation process [19], we first carried out a pretest with a representative sample of the target population, to assess the comprehensibility of the questions and their wording. [19] The psychometric validation procedure showed this questionnaire was valid, consistent and reliable.…”
Section: Recruitmentmentioning
confidence: 99%
“…Some studies investigated whether sets of items on different types of behaviours (e.g., hand washing, social distancing and wearing a face mask) jointly measure a latent construct of 'adherence', but did not study whether the individual items themselves adequately reflected participant behaviour (9)(10)(11). Other studies have assessed the reliability of self-reported behaviour by comparing it to objective data, but only for a specific behaviour such as mobility (12) or vaccination (3), or in specific contexts such as among healthcare professionals (13).…”
Section: Introductionmentioning
confidence: 99%